Ex Situ conservation of plant genetic resources: Training module - Jaramillo, S.; Baena, M. (2007)
Plant genetic resources form the basis on which humankind subsists. They provide basic needs and help solve problems such as hunger and poverty. However, they are being lost, mainly through inappropriate use and destruction of habitat. Given their vital importance, we must conserve them for the benefit of both present and future generations. Plant genetic resources can be conserved within or outside their natural habitats, or by combining the two alternatives. Outside their natural habitats, plant genetic resources are conserved in germplasm collections and genebanks, going through different stages and procedures that require trained staff. To help train personnel in managing genebanks, Bioversity International has developed this teaching manual as part of a collaborative project with Spain to promote the training and research of plant genetic resources in Latin America. The text trains users in the fundamental aspects of ex situ conservation of plant genetic resources, that is, from collecting to germplasm use. It explains principles and describes the procedures needed for effective ex situ conservation. It also includes bibliographic references and examples that illustrate how to move from theory to practice. By developing and making this material available to users, Bioversity International hopes to significantly contribute to the training of technicians in plant genetic resources, thereby making them more efficient in ex situ conservation and germplasm use.